Torn apart how the child welfare system destroys black families - and how abolition can build a safer world - Roberts, Dorothy E. 1956- (Basic Books, 2023)
Introduction: A benevolent terror -- Black family destruction -- "They separate children at the Harlem border, too" -- Professional kidnappers -- Rotten at the root -- Strong-armed -- The foster industrial complex -- Family suerveillance -- Carceral entaglements -- Structured to harm -- The thin line -- Care in place of terror
Keywords: Jugendhilfe; USA; Child welfare / Government policy / United States; African American families / Government policy; African American families / Social conditions; Racism in social services / United States; Social work with African American children